North Atlantic controlled depositional cycles in MIS 5e layered sediments from the deep Dead Sea basin. Issue 1 (6th February 2017) - Palchan, Daniel; Neugebauer, Ina; Amitai, Yael; Waldmann, Nicolas D.; Schwab, Markus J.; Dulski, Peter; Brauer, Achim; Stein, Mordechai; Erel, Yigal; Enzel, Yehouda
Abstract: The drilled Inter-Continental Drilling Project core at the deeps of the Dead Sea reveals thick sequences of halite deposits from the last interglacial period, reflecting prevailing arid conditions in the lake's watershed. Here, we examine sequences of intercalating evaporates (halite or gypsum) and fine-detritus laminae and apply petrographic, micro-X-ray fluorescence, and statistical tools to establish in high-temporal resolution the hydroclimatic controls on the sedimentation in the last interglacial Dead Sea. The time series of the thickness of the best-recovered core sections of the layered halite, detritus, and gypsum reveals periodicities of 11, 7–8, and 4–5 yr, pointing to a North Atlantic control and possibly solar influence on the hydrology of the Dead Sea watershed during the regionally arid period of the last interglacial period. Similar periodicities were detected in the last glacial and modern sedimentary sequences of the Dead Sea and other archives of the central Levant, indicating a persistent impact of the solar cycles on regional hydrology, possibly through the effects of the North Atlantic Oscillation.